Utilization, Phytochemistry and Biological Activity of Hua gabonii Pierre ex De Wild. - Clément Mutunda Mbadiko; Gédéon Ngiala Bongo; Jean-Paul Koto-te-Nyiwa Ngbolua; Marie Claire Dembo D’A Letshu Yandju; Pius Tshimankinda Mpiana; Théophile Fundu Mbemba (Borneo Journal of Pharmacy, 2023)
Although few studies are reported, Hua gabonii remains scientifically unknown due to the lack of studies. However, this aromatic plant is used in developing countries as a condiment or in traditional medicine to treat various ailments. The literature reported that this species is rich in proteins, essential amino acids, and vitamins C and E. Its fruits would present an appreciable antioxidant power. Therefore, given its numerous uses in tropical countries, H. gabonii is a good candidate for further studies.